2022
DOI: 10.1093/cei/uxac006
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles containing PD-L1 contribute to CD8+ T-cell immune suppression and predict poor outcomes in small cell lung cancer

Abstract: Programmed death ligand-1 (PD-L1) is expressed on the surface of tumor cells and binds to programmed cell death protein-1 (PD1) on the surface of T cells, leading to cancer immune evasion via inhibition of T cell function. One of the characteristics of small cell lung cancer (SCLC) is its ineffective anti-tumor immune response and highly immunosuppressive status in the tumor microenvironment. SCLC cells have been shown to generate extracellular vesicles (EVs), which may play an important role in tumor progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Therapy using EVs derived from cancer cells has gained popularity since it contains cancer antigens and induces a cancer antigen-specific immune response, which provides an anti-tumour effect [ 289 ]. Although inducing anti-tumour immunity using cancer-cell-derived EVs has been reported, the effect remains to be verified.…”
Section: Ev-based Vaccine Therapy For Cancermentioning
confidence: 99%
“…Therapy using EVs derived from cancer cells has gained popularity since it contains cancer antigens and induces a cancer antigen-specific immune response, which provides an anti-tumour effect [ 289 ]. Although inducing anti-tumour immunity using cancer-cell-derived EVs has been reported, the effect remains to be verified.…”
Section: Ev-based Vaccine Therapy For Cancermentioning
confidence: 99%
“…Importantly, an anti-PD-L1 blocking antibody significantly reversed the EV-mediated inhibition of CD8+ T-cell activation, suggesting a prognostic values PD-L1 + ve EVs in predicting the effectiveness of therapy detection, as well as a new strategy to enhance T-cell-mediated immunotherapy against SCLC cancers. When tested on another lung cancer cohort, the presence of EVs containing PD-L1 significantly correlated with the progression-free survival of patients on immunotherapy [ 126 ]. PD-L1 expressed on the EVs, not the soluble form of PD-L1, is also shown to be associated with disease progression in head and neck cancer [ 127 ].…”
Section: Other Biomarkersmentioning
confidence: 99%
“…In numerous studies, the presence of specific T cell subtypes, NK cells and other myeloid cells have been associated with the prediction of response to IO. Several clinical trials have also reported detecting PD-L1, PD-L2, and PD1 expression on either CTCs or circulating immune cells to predict the response to the IO [ 25 , 38 , 126 ]. However, the data are insufficient to clearly show the predictive power for IO.…”
Section: Challenges In Liquid Biopsy-based Biomarker Developmentmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 13, 2022. ; https://doi.org/10.1101/2022.10.12.511984 doi: bioRxiv preprint immunosuppressive effects, inhibiting CD8+ T-cells by carrying PD-L1 22 . In the brain, microvascular endothelial cell-derived EVs can promote SCLC survival, potentially contributing to the high rate of SCLC metastasis to the brain 23 .…”
Section: Introductionmentioning
confidence: 99%